2010
DOI: 10.1088/0953-4075/43/8/085004
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime measurements and transition probabilities in Mo II

Abstract: Lifetimes have been measured using time-resolved laser-induced fluorescence for 16 odd levels in the doublet, quartet and sextet systems of Mo II, with energies in the range 48 000-61 000 cm −1 . Absolute transition probabilities and oscillator strengths are determined for 110 UV and visible transitions (208 < λ < 485 nm) from a combination of experimental lifetimes and theoretical branching fractions. The theoretical results are obtained using the HFR method including core polarization effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 17 publications
0
21
3
Order By: Relevance
“…The lifetimes of the levels at 48 022.82 and 60 992.76 cm −1 , which were investigated previously by Hannaford and Lowe [7], Sikström et al [8] and by Lundberg et al [10], respectively, were also measured in the present paper for comparison. Corresponding theoretical lifetime values were also calculated using the multiconfigurational HFR method taking core-polarization effects into account, and they are in good agreement with the experimental results having in mind the complexity of the calculations in such heavy atomic systems.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…The lifetimes of the levels at 48 022.82 and 60 992.76 cm −1 , which were investigated previously by Hannaford and Lowe [7], Sikström et al [8] and by Lundberg et al [10], respectively, were also measured in the present paper for comparison. Corresponding theoretical lifetime values were also calculated using the multiconfigurational HFR method taking core-polarization effects into account, and they are in good agreement with the experimental results having in mind the complexity of the calculations in such heavy atomic systems.…”
Section: Introductionmentioning
confidence: 63%
“…[15]). As the physical model considered was exactly the same as the one described in our recent study of Mo II [10], the details will not be repeated here. Let us just remind that, in the latter work, the configurations 4d 5 , 4d 4 5s, 4d 4 6s, 4d 4 5d, 4d 3 5s 2 , 4d 3 5p 2 , 4d 3 5d 2 , 4d 3 5s5d (even parity) and 4d 4 5p, 4d 4 6p, 4d 4 4f , 4d 4 5f , 4d 3 5s5p, 4d 3 5p5d (odd parity) were included in the calculations with the dipole polarizability α d = 5.67a 3 0 and the cut off radius r c = 1.73a 0 as corepolarization parameters.…”
Section: Theoretical Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to fill in this gap, in the present paper, we report on calculations of oscillator strengths and transition probabilities in this ion performed using the HFR approach including core-polarization effects. This work is an extension of our recent investigations of the fifth row elements Rb III (Zhang et al 2014), Y II, Y III (Biémont et al 2011), Zr II (Malcheva et al 2006), Nb I (Malcheva et al 2011), Nb II, Nb III (Nilsson et al 2010), Mo II (Quinet 2002, Lundberg et al 2010, Jiang et al 2012, Tc II (Palmeri et al 2007), Ru I (Fivet et al 2009), Ru II, Ru III (Palmeri et al 2009), Rh II (Quinet et al 2011(Quinet et al , 2012, Rh III (Zhang et al 2013a), Pd I (Xu et al 2006), Pd III (Zhang et al 2013a), Ag II (Biémont et al 2005, Campos et al 2005, Ag III (Zhang et al 2013a), Sn I (Zhang et al 2008(Zhang et al , 2009(Zhang et al , 2010, Sb I (Hartman et al 2010), Te II and Te III (Zhang et al 2013b).…”
Section: Introductionmentioning
confidence: 74%
“…With the HFR approach including core-polarization effects, theoretical lifetimes for 37 levels of Mo II and the oscillator strengths of the depopulating transitions were calculated by Quinet (2002). More recently, Lundberg et al (2010) measured new radiative lifetimes for 14 odd levels in the energy range 48000-61000 cm −1 while Jiang et al (2012) reported experimental values for 13 odd levels between 48022 and 63497 cm −1 . In these two latter works, new transition probabilities were also obtained using the HFR method.…”
Section: Introductionmentioning
confidence: 99%